Immunogenicity and Efficacy in Aotus Monkeys of Four Recombinant Plasmodium falciparum Vaccines in Multiple Adjuvant Formulations Based on the 19-Kilodalton C Terminus of Merozoite Surface Protein 1 - Kumar, Sanjai (American Society for Microbiology, 2000)
The immunogenicity and protective efficacy of four versions of recombinant C-terminal 19-kDa epidermal growth factor-like region of the major surface protein 1 (rMSP1(19)) of Plasmodium falciparum was studied in Aotus monkeys. Vaccination with each of the four rMSP1(19) constructs elicited high levels of antibodies to MSP1(19) but only one construct, the 19-kDa fragment expressed as a secreted fusion protein from Saccharomyces cerevisiae (yP30P2MSP1(19)), induced a high degree of protective immunity in Aotus nancymai against lethal P. falciparum challenge. Protective formulation required Freund's adjuvant; vaccination with yP30P2MSP1(19) in six other adjuvants that are suitable for human use induced lower levels of antibody response and no protection. These results emphasize the need to continue the search for an adjuvant that is comparable to Freund's adjuvant in potency and is safe for use in humans.